A Literature Review of Northern Thai Local Vegetable Studies by Thai Scholars (1985–2025) Toward Developing Community Landscape Architecture Design Approaches Based on Local Wisdom - Amloy, Aumpika; Maneesatit, Paworn; Preechom, Sasipim (Journal of Landscape Architecture and Planning, 2025)
Northern Thai native vegetables are vital biological resources with multidimensional significance in food, health, culture, and landscape. They embody local wisdom transmitted across generations through consumption, culinary practices, and medicinal uses. Academic studies from 1985 to 2025 have explored these vegetables in diverse aspects, ranging from ethnobotanical surveys and nutritional studies to their role in creative economy and gastronomy tourism. However, research that integrates native vegetables into landscape architectural perspectives remains limited. This review article thus aims to (1) examine the body of literature on Northern Thai native vegetables conducted by Thai scholars over the past four decades (1985–2025), and (2) synthesize design approaches for community landscape architecture grounded in local wisdom. The study employed a literature review methodology, collecting selected scholarly works from recognized databases, including the Thai Digital Collection (TDC), Thai Journals Online (ThaiJO), the National Research Council of Thailand (NRCT), and the Thailand Science Research and Innovation (TSRI) portal, as well as peer-reviewed journals. The reviewed works were categorized into four key dimensions: (1) health and nutrition, (2) local wisdom and cultural heritage, (3) creative economy and gastronomy tourism, and (4) biodiversity and plant conservation. The findings reveal a continuous progression from fundamental ethnobotanical documentation to applied studies in health promotion and creative economy, while also highlighting the opportunity to integrate native vegetables into community landscape design. Practical approaches include Community Health Gardens, Miang & Spice Gardens, and Cultural Food Courts, which can connect dietary, medicinal, and cultural values to public space design. This article concludes that integrating Northern Thai native vegetables into community landscape architecture based on local wisdom provides not only a strategy for plant genetic conservation and cultural identity preservation but also a pathway to promote community health, cultural resilience, and sustainable creative economy development.